www-based monitoring and control for over-stressed river basins - Hansen, Roger D., author; Berger, Bret, author; Hilton, Arlen, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
The Bureau of Reclamation (Reclamation), StoneFly Technology (StoneFly), Utah State University (USU), and several Utah water user groups are working to create "virtual" river basins on the Internet. Websites with accurate real-time representations of the Sevier, San Rafael, and Duchesne river basins are being developed. These river basin websites, coupled with low-cost automatic remote-control on all major structures, allow for nearly instantaneous decision-making. The ability to see what is happening throughout a river basin and to react promptly to changing hydrologic and weather conditions is dramatically improving the way rivers and irrigation canals are operated. Additionally, these websites are important elements in building trust and encouraging collaboration between the various stakeholders.
USCID/EWRI conference
River basin websites
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.